2020
DOI: 10.3389/fpls.2020.572848
|View full text |Cite|
|
Sign up to set email alerts
|

Exocytosis and Endocytosis: Yin-Yang Crosstalk for Sculpting a Dynamic Growing Pollen Tube Tip

Abstract: The growing pollen tube has become one of the most fascinating model cell systems for investigations into cell polarity and polar cell growth in plants. Rapidly growing pollen tubes achieve tip-focused cell expansion by vigorous anterograde exocytosis, through which various newly synthesized macromolecules are directionally transported and deposited at the cell apex. Meanwhile, active retrograde endocytosis counter balances the exocytosis at the tip which is believed to recycle the excessive exocytic component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…However, what is the biological role of autophagy during this process? We know that large numbers of mitochondria are required for rapidly growing pollen tubes to support the energy demands of metabolism, cell growth and transport related functions [ 2 , 5–7 ]. The autophagy of mitochondria as a general means of cellular quality control is also a well-studied phenomenon.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, what is the biological role of autophagy during this process? We know that large numbers of mitochondria are required for rapidly growing pollen tubes to support the energy demands of metabolism, cell growth and transport related functions [ 2 , 5–7 ]. The autophagy of mitochondria as a general means of cellular quality control is also a well-studied phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…Pollen tubes are one of the fastest growing cell types in nature. To support the rapid and sustainable pollen tube growth, high levels of energy production is required to support the active metabolism and vigorous intracellular transport [ 2 , 4 , 5 ]. The number of mitochondria in pollen is about 20-fold greater compared to vegetative cells in maize [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The polar growth of the pollen tube is achieved via complex mechanisms, which involve the tight coordination between endocytosis and exocytosis, plant-specific Rho GTPase ROP1, the actin cytoskeleton, exocyst complex, phospholipids, SNARE proteins, cell wall biochemical mechanics, Ca 2+ , pH and reactive oxygen species (ROS) (Fig. B2) [58]. The apical region of the pollen tube is divided into the apex, subapical and shank regions.…”
Section: Endocytosis In Pollen Tubesmentioning
confidence: 99%
“…cerevisiae , endocytosis forms a ring around the secretion site at the time of bud emergence [ 7 , 8 ]; in filamentous fungi, the zone of endocytosis is largely distinct from the secretion zone, forming a collar around the exocytic apical zone (reviewed in [ 9 ]). Similarly, exo‐ and endocytosis sites overlap at the apex of pollen tubes [ 10 ], but these display a clear sub‐apical region where endocytosis takes place [ 11 , 12 ], suggesting an organization very similar to that observed in filamentous fungi. In this configuration, computational simulations showed that membrane flows would occur even without net membrane growth [ 1 ].…”
Section: Conditions To Generate Bulk Membrane Flowsmentioning
confidence: 99%